SISTEM INFORMASI PELAPORAN DOWNTIME PRODUKSI DI PT APPAREL ONE INDONESIA 2 - Ikhsan, Ardani Yanuar; Nugroho, Isworo (MEANS (Media Informasi Analisa dan Sistem), 2022)
To create production downtime report-making using an information system at PT. Apparel One Indonesia 2 is still very important to investigate daily production time. Moreover, this report is also used to find out some of the problems that occur every day so that the company can prevent the occurrence of same problem in the future. So, it is expected that the problem will be resolved more effectively in reporting production downtime in PT. Apparel One Indonesia 2. Currently, the company’s reporting process is still manual, using the paper and then inputting to Microsoft Excel software by the administrator. This makes the administrator takes longer time for making the production of production downtime reports and requires a lot of paper to make. The risk of misreporting all the company’s problems and processes is also high. The downtime reporting using information system has been successfully implemented. It is expected that the built of information system can be used for faster and more accurate data processing. This information system produces several reports, including production downtime reports, borrowing reports (machines, needles, and spare parts), expenditure reports, return reports and stock reports (machines), needles, and spare parts) which are useful for monitoring so that downtime is minimized. The results of the questionnaire test from the built PKK information system were measured using a Likert scale, and the results were 95% in the very satisfied category.